1998
DOI: 10.1021/jf971007b
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Inhibitor Activity in Field Pea (Pisum sativum L.) and Grass Pea (Lathyrus sativus L.)

Abstract: Trypsin inhibitors in grain legumes decrease the digestibility of protein and cause pancreatic enlargement. Seed samples of 17 field pea cultivars grown at 5 locations and 9 grass pea lines grown at 2 locations in western Canada during 1993 and 1994 were analyzed for trypsin inhibitor activity (TIA). TIAs in field pea differed significantly among cultivars. Mean TIA in field pea ranged from 2.22 trypsin inhibitor unit (TIU) mg-1 of dry matter (DM) for Danto to 7.66 TIU mg-1 of DM for Baroness. Cultivar account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…Content of these ANFs in the studied L. sativus accessions (average 3.3 kg -1 DM) was close to the level determined by Wang et al (1998) and 3 times higher in comparison with the results reported by Deshpande and Campbell (1992) but twice lower than in grass pea seeds evaluated by Urga et al (2005). Similarly to Deshpande and Campbell (1997), tannin concentration was significantly (P \ 0.05) correlated with the color of flowers (r = 0.64) as well as the colour of their seeds (r = 0.69), noteworthy darker colours are associated with generally higher levels of tannins.…”
Section: Discussionsupporting
confidence: 88%
“…Content of these ANFs in the studied L. sativus accessions (average 3.3 kg -1 DM) was close to the level determined by Wang et al (1998) and 3 times higher in comparison with the results reported by Deshpande and Campbell (1992) but twice lower than in grass pea seeds evaluated by Urga et al (2005). Similarly to Deshpande and Campbell (1997), tannin concentration was significantly (P \ 0.05) correlated with the color of flowers (r = 0.64) as well as the colour of their seeds (r = 0.69), noteworthy darker colours are associated with generally higher levels of tannins.…”
Section: Discussionsupporting
confidence: 88%
“…In Poland, although grasspea has been consumed for hundreds of years, not a single case of the disease has been recorded to date. Numerous research reports present the defi nite conclusion that biologically-active compounds are an important element of the prophylaxis and control of civilisation diseases and should not be eliminated from food [Hanbury et al, 2000;Srivastava & Khokhar, 1996;Wang et al, 1998]. …”
Section: Introductionmentioning
confidence: 99%
“…a-Galactosides, phytates and trypsin inhibitors are among these factors, and their concentrations differ widely among different cultivars of peas [5]. One proteinaceous component of peas that has received considerable attention as a quality determinant is that which complexes with the intestinal protease trypsin; the component is thus referred to as trypsin inhibitor [6]. A number of protease inhibitors have been isolated from peas.…”
Section: Introductionmentioning
confidence: 99%